2021
DOI: 10.3324/haematol.2020.261354
|View full text |Cite
|
Sign up to set email alerts
|

The <i>EBF1-PDGFRB</i> T681I mutation is highly resistant to imatinib and dasatinib <i>in vitro</i> and detectable in clinical samples prior to treatment

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“… 16 In contrast to our data, previous studies have suggested sensitivity to dasatinib in Ba/F3 models expressing PDGFRB -fusions. 4 , 60 , 61 Moreover, various case reports of patients with PDGFRB -fused ALL indicated a response to dasatinib. 5 , 35 , 40 However, multiple studies using kinase selectivity assays have shown a lower affinity of dasatinib for wild-type PDGFRB than for BCR::ABL1 or wild-type ABL1.…”
Section: Discussionmentioning
confidence: 99%
“… 16 In contrast to our data, previous studies have suggested sensitivity to dasatinib in Ba/F3 models expressing PDGFRB -fusions. 4 , 60 , 61 Moreover, various case reports of patients with PDGFRB -fused ALL indicated a response to dasatinib. 5 , 35 , 40 However, multiple studies using kinase selectivity assays have shown a lower affinity of dasatinib for wild-type PDGFRB than for BCR::ABL1 or wild-type ABL1.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of clinical evidence from case reports or small patient series to confirm the preclinical efficacy of ABL and JAK inhibitors in Ph-like ALL [86][87][88] . Preclinical and clinical reports have also demonstrated the sensitivity of NTRK inhibitor, larotrectinib, or ALK inhibitor, crizotinib, for the rare ETV6-NTRK3 Ph-like ALL [19,89,90] . Recently, mutations conferring resistance to imatinib and dasatinib have been identified in relapsed EBF1-PDGFRB Ph-like ALL, raising the necessity to monitor kinase domain mutations over the course of therapy to guide TKI selection [91] .…”
Section: Ph-like Allmentioning
confidence: 99%
“…They identified the mutation in three of 23 patients prior to treatment. 12 We speculate that mutations which confer resistance but reduce kinase activity or transformative capacity would not outgrow before TKI treatment and therefore only a subset of resistance mutations can exist in therapy-naïve patients. The high turnover rate of ALL cells should allow a much faster selection of mutated clones with a relative growth advantage if compared to the situation in chronic myeloid leukemia.…”
mentioning
confidence: 94%